leosh

5 Reputation

One Badge

3 years, 302 days

MaplePrimes Activity


These are questions asked by leosh

 

equ1 := -l*cos(xi)^2*(1-cos(`β__f`))/(alpha^2.sin(sigma))-`λ__2`*w*(v^2.sin(sigma))/(g*l*cos(xi)^2) = 0

-l*cos(xi)^2*(1-cos(`β__f`))/(alpha^2.sin(sigma))-`λ__2`*w*(v^2.sin(sigma))/(g*l*cos(xi)^2) = 0

(1)

equ2 := -l*cos(xi)^2*(1-cos(beta[f]))/(alpha*sin(sigma)*tan(sigma))+Typesetting:-delayDotProduct(l, cos(xi)^2)*z__0*sin(`β__f`)/(alpha*sin(sigma)*(2*l*cos(sigma)^2))-`λ__1`*`#mi("L")`*`#mi("sin",fontstyle = "normal")`(sigma)*cos(xi)+`λ__2`*L*cos(sigma)*cos(xi)-`λ__2`*w*alpha*v^2*sin(sigma)/(g*l*tan(sigma)*cos(xi)^2) = 0

-l*cos(xi)^2*(1-cos(beta[f]))/(alpha*sin(sigma)*tan(sigma))+(1/2)*(l.(cos(xi)^2))*z__0*sin(`β__f`)/(alpha*sin(sigma)*l*cos(sigma)^2)-`λ__1`*`#mi("L")`*`#mi("sin",fontstyle = "normal")`(sigma)*cos(xi)+`λ__2`*L*cos(sigma)*cos(xi)-`λ__2`*w*alpha*v^2*sin(sigma)/(g*l*tan(sigma)*cos(xi)^2) = 0

(2)

equ3 := l*cos(xi)^2*sin(`β__f`)*tan(sigma)/(alpha*sin(sigma)*(2*l)) = 0

(1/2)*cos(xi)^2*sin(`β__f`)*tan(sigma)/(alpha*sin(sigma)) = 0

(3)

equ4 := -`λ__1`*`#mi("L")`*`#mi("cos",fontstyle = "normal")`(sigma)*sin(xi)+`λ__2`*L*sin(sigma)*sin(xi)-2*`λ__2`*tan(xi)*w*alpha*v^2*sin(sigma)/(g*l*cos(xi)^2)-l*sin(2*xi)*(1-cos(beta[f]))/(alpha*sin(sigma)) = 0

-`λ__1`*`#mi("L")`*`#mi("cos",fontstyle = "normal")`(sigma)*sin(xi)+`λ__2`*L*sin(sigma)*sin(xi)-2*`λ__2`*tan(xi)*w*alpha*v^2*sin(sigma)/(g*l*cos(xi)^2)-l*sin(2*xi)*(1-cos(beta[f]))/(alpha*sin(sigma)) = 0

(4)

equ5 := L*cos(sigma)*cos(xi)-w = 0

L*cos(sigma)*cos(xi)-w = 0

(5)

`#mi("equ6")` := `#mi("L")`*`#mi("sin",fontstyle = "normal")`(sigma)*cos(xi)-w*alpha*v^2*sin(sigma)/(g*l*cos(xi)^2)

`#mi("L")`*`#mi("sin",fontstyle = "normal")`(sigma)*cos(xi)-w*alpha*v^2*sin(sigma)/(g*l*cos(xi)^2)

(6)

answer := solve({equ1, equ2, equ3, equ4, equ5, equ6}, {alpha, sigma, xi, `λ__1`, `λ__2`, beta[f]})

``

(7)

``

(8)

NULL

 

Download Bryson_sesson1_p6.mw

 

equ1 := -l*cos(gamma)^2*(1-cos(`β__f`))/(alpha^2*sin(sigma))-`λ__2`*w*v^2*sin(sigma)/(g*lcos(gamma)^2) = 0

-l*cos(gamma)^2*(1-cos(`β__f`))/(alpha^2*sin(sigma))-`λ__2`*w*v^2*sin(sigma)/(g*lcos(gamma)^2) = 0

(1)

equ2 := -l*cos(gamma)^2*(1-cos(beta[f]))/(alpha*sin(sigma)*tan(sigma))+l*cos(gamma)^2*z__0*sin(`β__f`)/(alpha*sin(sigma)*(2*l*cos(sigma)^2))-`λ__1`*`#mi("L")`*sin(sigma)*cos(gamma)+`λ__2`*L*cos(sigma)*cos(gamma)-`λ__2`*`wα`*v^2*sin(sigma)/(g*l*tan(sigma)*cos(gamma)^2) = 0

-l*cos(gamma)^2*(1-cos(beta[f]))/(alpha*sin(sigma)*tan(sigma))+(1/2)*cos(gamma)^2*z__0*sin(`β__f`)/(alpha*sin(sigma)*cos(sigma)^2)-`λ__1`*`#mi("L")`*sin(sigma)*cos(gamma)+`λ__2`*L*cos(sigma)*cos(gamma)-`λ__2`*`wα`*v^2*sin(sigma)/(g*l*tan(sigma)*cos(gamma)^2) = 0

(2)

equ3 := l*cos(gamma)^2*sin(`β__f`)*tan(sigma)/(alpha*sin(sigma)*(2*l)) = 0

(1/2)*cos(gamma)^2*sin(`β__f`)*tan(sigma)/(alpha*sin(sigma)) = 0

(3)

equ4 := -`λ__1`*`#mi("L")`*cos(sigma)*sin(gamma)+`λ__2`*L*sin(sigma)*sin(gamma)-2*`λ__2`*tan(gamma)*`wα`*v^2*sin(sigma)/(g*lcos(gamma)^2)-l*sin(2*gamma)*(1-cos(beta[f]))/(alpha*sin(sigma)) = 0

-`λ__1`*`#mi("L")`*cos(sigma)*sin(gamma)+`λ__2`*L*sin(sigma)*sin(gamma)-2*`λ__2`*tan(gamma)*`wα`*v^2*sin(sigma)/(g*lcos(gamma)^2)-l*sin(2*gamma)*(1-cos(beta[f]))/(alpha*sin(sigma)) = 0

(4)

equ5 := L*cos(sigma)*cos(gamma)-w = 0

L*cos(sigma)*cos(gamma)-w = 0

(5)

equ6 := `#mi("L")`*sin(sigma)*cos(gamma)-`wα`*v^2*sin(sigma)/(g*l*cos(gamma)^2)

`#mi("L")`*sin(sigma)*cos(gamma)-`wα`*v^2*sin(sigma)/(g*l*cos(gamma)^2)

(6)

answer := solve({equ1, equ2, equ3, equ4, equ5, equ6}, {alpha, gamma, sigma, `λ__1`, `λ__2`, beta[f]})

Error, (in solve) a constant is invalid as a variable, gamma

 

``


how can i solve this problem?

Download Bryson_sesson1_p6.mw

Page 1 of 1